Volumetric–Densimetric Measurements of the Adsorption Equilibria of Binary Gas Mixtures - J.U. Keller; N. Iossifova; W. Zimmermann (Adsorption Science & Technology, 2005)
A new method for measuring the binary co-adsorption equilibria of gas mixtures with non-isomeric components on porous solids such as activated carbons or zeolites is proposed. The method does not require an analysis of the sorptive gas phase in adsorption equilibrium and can be automated fairly simply. It consists of a simple volumetric/manometric gas expansion arrangement combined with the measurement of the density of the sorptive gas mixture in equilibrium via the buoyancy of a sinker fixed to a microbalance. These gas density measurements can be performed on-line preferably with a magnetic suspension balance (MSB) (Rubotherm GmbH, Bochum, Germany, 2-site-type). The experimental lay-out of the instrument used is given and the measurement procedure is outlined. The theory of the measurement is presented and expressions for experimental uncertainties of component masses adsorbed are provided. As examples, the co-adsorption equilibria data of gas mixtures (CO 2 /CH 4 ) and (H 2 /CH 4 ) on activated carbon (D47/3, CarboTech, Essen, Germany) at 293 K and 333 K for pressures up to 2 MPa are presented and discussed to a certain extent.